Designing and standardizing the testing battery for bioactive capabilities as an indicator for the selection of the volunteers of the Commissioners Preparation Institute - SAAD GHAZl HASAN AL. BATTBOOTTl,; Asst. Prof. Dr. ALAA FLAYYlH JAWAD;,; Asst. Prof. Dr. Rafid Saad Hadi,; Asst. Prof. Dr.Atheer khaleel Ibrahim Alsudani, (International Journal of Psychosocial Rehabilitation, 2020)
The research problem lies in the lack of special biomechanical tests in the field of physical training to update the test batteries in a way that simulates the requirements and their field developments, and the research aims to design and standardize the test battery for biomechanical abilities as an indicator for the selection of the volunteers of the Institute for Preparing Commissioners. The researchers adopted the descriptive approach. Institute for the preparation of commissioners, the number of (400) students, biomechanical tests that are compatible with the research requirements were identified and nominated (15) A test, exploratory experiments were conducted, and appropriate statistical treatments were conducted, including a matrix of correlation coefficients for all variables and a factor analysis using the basic components method using the slanted rotation. On the rationing sample, the researcher extracted the standard scores, and the study reached some conclusions, the most important of which are: The factor analysis of the inter-correlation matrix of the variables for the biomechanical tests enabled the researcher to reach (5) factors, to arrive at setting standards scores for biomechanical tests as a means of evaluation, evaluation and interpretation that can be relied upon to select The volunteers of the Institute for the Preparation of Commissioners and in light of the conclusions the researcher recommended: The use of the battery concerned with measuring biomechanical tests extracted internationally as objective methods for measuring and evaluating the capabilities of the volunteers of the institute of preparing commissioners, from the results of the current study, especially the criteria in light of the classification of the capabilities of the volunteers of the institute of preparing commissioners.